Wood Microstructure of Indian Maytenus molina (Celastraceae) with Special Reference to Ecology - Saxena, Vishakha; Gupta, Sangeeta (Indian Forester, 2010)
The present study deals with the detailed wood microstructure of the genus Maytenus Molina (syn. Gymnosporia W. & A.) belonging to the family Celastraceae. Five species of Maytenus has been described on the basis of their detailed microstructure, salient diagnostic features and photomicrographs. An identification key based on anatomical features has been developed for the separation of the species of this genus. According to the present study M. emarginata (Willd.) DingHou and M. senegelensis (lam.) Exell could not be separated due to the same anatomy. This study is the first record of the wood microstructure of this genus. The correlation between selected wood anatomical features (qualitative and quantitative) and vegetation type (tropical and temperate) has been discussed in this paper. Inverse relationship was observed between vessel diameter and vessel frequency indicating conductive efficiency of this genus. Positive relationship between vessel frequency and vessel length was observed in tropical species while inverse relationship in temperate species. F/V and L/D ratios were found to be inversely correlated.